POTENSI CENDAWAN MIKORIZA ARBUSKULA UNTUK MENINGKATKAN HASIL TANAMAN JAGUNG - Musfal Musfal (Jurnal Penelitian dan Pengembangan Pertanian, 2010)
Potential of vesicular arbuscular mycorrhiza in increasing maize yieldVesicular arbuscular mycorrhizae ( VAM ) can associate and symbiose with 97% high level plant family. VAM is included in ordo Glomales, and based on the body structure and infection way can be grouped into endomycorrhizae and ectomycorrhizae. VAM is able to improve the physical and chemical properties of soil, increase nutrient absorption, improve plant resistance to drought, protect roots from pathogens, increase plant yield, and release the P fixation. Ectomycorrhizae fungi can be consumed and as medicine. Application of VAM up to 20 g/plant and 100% NPK dosage in Inceptisols affected root infection, P absorption, biomass weight, and increased maize yield. P absorption was positively correlated with the maize yield. VAM reduced the rate of NPK fertilizer up to 50%. Application of 50% NPK fertilizer added with VAM 15 g/plant produced maize yield that was not significantly different with application of 100% NPK fertilizer. The highest maize yield was produced with application of 100% NPK fertilizer added with VAM 20 g/plant.Keywords: Zea mays, vesicular arbuscular mycorrhizae, yield